Longitudinal examination of cervical volume and vascularization changes during the antepartum and postpartum period using three-dimensional and power Doppler ultrasound - (:unkn) unknown (My University, 2010)
OBJECTIVE: To assess longitudinally the changes in cervical volume and vascularization during the peripartum period using three-dimensional ultrasound (3D US) and power Doppler and to determine whether these measures change with gestational complications. METHODS: Longitudinal measurements of cervical dimensions by transvaginal 3D US and power Doppler using the virtual organ computer-aided analysis program were performed at 11-14, 22-24, 32-34 weeks' gestation, and at 6 weeks' postpartum in 111 pregnant women. Comparisons were made between women who delivered at term (vs. preterm), nulliparous (vs. parous), with (vs. without) pre-eclampsia and those with (vs. without) gestational diabetes. RESULTS: After establishing reference values for each peripartum period for cervical volume, vascularization index (VI) and flow index (FI), we found that the 2(nd) and 3(rd) trimester volume, 2(nd) trimester FI and postpartum VI were different in nulli- vs. multiparous women. Volume and vascularization parameters were unaffected by preterm labor. Second trimester VI and vascularization flow index values were lower in pre-eclamptic vs. non-pre-eclamptic women (P<0.05), but unaffected by gestational diabetes. CONCLUSION: Cervical volume and vascularization parameters are not helpful in predicting preterm labor and gestational diabetes, but might be associated with pre-eclampsia.
Keywords: Adult; Female; Humans; Pregnancy; Young Adult; Cervix Uteri; Predictive Value of Tests; Longitudinal Studies; Ultrasonography, Doppler; Parity; Diabetes, Gestational; Pregnancy Trimester, First; Postpartum Period; Pre-Eclampsia; Pregnancy Trimester, Third; Obstetric Labor, Premature; Pregnancy Trimester, Second